KANDUNGAN LOGAM Pb DI SUNGAI DELI PROVINSI SUMATERA UTARA (The content of Pb metal in Deli River, North Sumatera Province) - Paulus Surbakti; Pindi Patana; Riri Ezraneti (AQUACOASTMARINE, 2014)
Water is a natural resources that supplies the needs of many peoples life, so it certainly to be protected for human and other living organisms. Industrialization and rapid population growth, had a negative impact on the quality and the existence of natural resources and the environment, such as pollution of heavy metal. This research aims to analyze the content of Pb in the middle and lower Deli watershed and to determine the Deli water quality based on water quality standards.This study was conducted on July until August 2013 at Deli watershed of North Sumatra province. The number of point observed station are 4 stations . The aquatic parameters measured were physic and chemistry, concentrations of heavy metals Pb and Cu in the water column using Atomic Absorption Spectrophotometry ( AAS ) .The results showed Pb concentrations ranged from 0.079- 0.408 mg/l. This result shows that heavy metal of Pb in Deli watershed has exceeded the quality standard.Keywords : heavy metals Pb